SMALL AND MEDIUM SCALE ENTERPRISES SUSTAINABILITY IN A DEPRESSING ECONOMY: THE STRATEGIC ROLE OF NIGERIAN ACCOUNTANTS - NWINEE, KPURUGBARA,; AKPOS, YIKAREBOGHA, EROROGHA; UCHE, AHIUZU, LEVI (IJRDO - Journal of Applied Management Science, 2017)
This paper focused on examining Small and Medium Scale Enterprises Sustainabilityin a Depressing Economy: The Strategic Role of Nigerian Accountants. This study took adescriptive survey approach and data was sourced from the 177 completed and returned fivepoint likert scale questionnaire administered on accountants drawn from 40 SMEs in Rivers andEnugu State. T-test was used to analyze the data gathered with the aid of 20.0 version ofstatistical package for social sciences (SPSS). It was observed that SMEs in Nigeria arechallenged by the poor national economic outlook that is hampering their competitiveness andthreatening their sustainability. Hence, the study concludes that to satisfy the three bottom-lineor pillars of sustainability, Nigerian accountants must be made strategic internal partners inSMEs as they have very important roles to play especially in the areas of environmental andeconomic sustainability of the firms. It was recommended that SMEs should engage in theiremploy qualified accountants who can guide and advice it on financial matters in other toenhance their sustainability, Training of accountants on environmental disclosure is very key tothe sustainability of SMEs, There is need to ensure that SMEs do not just focus on immediategains when developing their strategies, they should as a matter of strategic importance inculcatesustainability components in their strategies